The experimental study on the correlation of resistivity and damage for conductive concrete. (March 2016) - Chu, Hong-yan; Chen, Jian-kang
Abstract: This paper investigates the correlation of conductivity and damage evolution in carbon fiber reinforced conductive concrete. Under axial static loading and quasi-static cycle loading, the damage evolution is detected by ultrasonic technique, and the variation of resistivity is also inspected using real-time measurement method. According to the stress wave theory, the relationship between the damage evolution in concrete and variation of ultrasonic velocity is obtained, eventually concluding in the correlation of concrete damage and its resistivity. The research results indicate that concrete real-time damage and resistivity exhibits cubic polynomial correlation under the condition of a static load, and concrete resistivity and residual damage shows exponential growth rule under the condition of a cyclic load.